Forms of professional interkinesthesia in nurses' body work: A case study of an infant's stepping - Katila, Julia; Philipsen, Johanne S. (Frontiers in Communication, 2022)
Moving their bodies in knowledgeable and professional ways in order to handle and connect affectively with infants entails a large part of child health care nurses’ work. We deploy a phenomenological approach to videoanalysis of interaction to analyze an episode of a 1-month-old infant visiting the child health care clinic with their caregiver to have their body assessed for a neonatal stepping. Focusing on the co-movement of the baby and the nurse, we ask: how do various ways of moving as a co-embodied entity allow and corporeally prompt the baby’s age-appropriate bodily ability to emerge? We develop the notion of professional interkinesthesia to indicate specific forms of body work of nurses which in this case entails moving together with the baby to make her successfully perform a specific health care task—the stepping. Building on Charles Goodwin’s (1994) concept of professional vision, we uncover how the nurse moves and touches the infant’s body in ways relevant to the institutional task. The study shows that accomplishing “normally” developed neonatal stepping is not work accomplished by the baby alone but requires that the bodies of the baby and the professional move in unison. While neonatal stepping is but one specific type of health care task, we propose that nurses’ work entails numerous forms of professional touch and interkinesthesia that make it possible to successfully perform different types of health care operations.